Patients' Experiences of Living with Coronavirus Disease 2019: A Qualitative Study - Zohreh Khoshnood; Roghayeh Mehdipour-Rabori; Faezeh Nazari Robati; Marzieh Helal Birjandi; Samaneh Bagherian (Mashhad University of Medical Sciences, 2021)
Background: The emergence of this coronavirus disease 2019 (COVID-19) is now a public health crisis that leads to various challenges. There is a significant scientific gap in this field, including the necessity of updating the definitions and information about this disease. This disease causes a lot of physical and psychological problems and leads to changes in and reduced quality of life. However, one of the definitive pieces of data about this disease is human-to-human transmission and its very high prevalence, which itself carries certain social and psychological risks. Aim: This study aimed to explore patients' experiences of living with COVID-19. Method: The present qualitative study was conducted based on a conventional content analysis method. The statistical population of this study (n=17) consisted of recovered patients from COVID-19 with a history of admission to the intensive care unit of Afzalipour Hospital in Kerman, Iran, selected using a purposive sampling method. The data were collected through semi-structured interviews and analyzed using the qualitative content analysis method proposed by Graneheim and Lundman. Results: Data collection and analysis led to the determination of 1 theme, 4 categories, and 18 subcategories. The theme was identified as "Coronavirus as a prison of time" and the categories were "behavioral challenges", "human flourishing", negative emotions", and "psychological distress in quarantine". Implications for Practice: Study participants had both positive and negative experiences. The results of this study can help healthcare providers to identify the needs of these patients and design a care model for these patients